2001
DOI: 10.1046/j.1440-6047.2001.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection of N‐methyl‐N′‐nitro‐N‐nitrosoguanidine‐induced in vivo clastogenicity by aqueous garlic extract

Abstract: The modulatory effects of garlic extract on the in vivo clastogenicity of N-methyl-N'-nitro-N-nitrosoguanidine (MNNG), a carcinogenic nitrosamine, were evaluated by quantification of micronuclei and chromosomal aberrations in metaphase cells from the bone marrow of male Wistar rats. A single intraperitoneal injection of MNNG (40 mg/kg bodyweight) was found to be clastogenic as revealed by the increased frequency of micronucleated polychromatic erythrocytes and chromosomal aberrations. Pretreatment with aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, dietary garlic supplementation was reported to reduce MNU-induced methylation of DNA in rat mammary gland (32). Treatment of rats with an aqueous garlic extract was also found to reduce N-methyl-N′-nitro-N-nitrosoguanidine (MNNG)-induced clastogenicity in bone marrow (33). The reason for these opposite findings in studies using direct-acting compounds is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, dietary garlic supplementation was reported to reduce MNU-induced methylation of DNA in rat mammary gland (32). Treatment of rats with an aqueous garlic extract was also found to reduce N-methyl-N′-nitro-N-nitrosoguanidine (MNNG)-induced clastogenicity in bone marrow (33). The reason for these opposite findings in studies using direct-acting compounds is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Lavelli et al (1999) reported that both fresh and air dried tomato extracts as well as processed tomatoes function as free radical scavengers in ROS-mediated reactions and in lipid peroxidation. Studies in this laboratory have demonstrated that tomato and garlic protect against the genotoxic effects of carcinogens by modulating lipid peroxidation and enhancing GSH-dependent antioxidants (Arivazhagan et al, 2000(Arivazhagan et al, , 2001b.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have also been shown to reduce the incidence of a multitude of chemically induced tumors in animal models. Pretreatment with aqueous garlic extract significantly reduced the frequencies of N-methyl-N 0 -nitro-N-nitrosoguanidine-induced micronuclei and chromosomal aberrations (Arivazhagan et al, 2001). These compounds have also been shown to reduce toxicity induced by thioacetamide, carbon tetrachloride, N-nitrosodimethylamine-and acetaminophen (all CYP2E1 substrates) in rodents (Ramaiah et al, 2001;Wang et al, 2000;.…”
Section: B Association Of Herb -Cyp Interactions With Chemoprotectivmentioning
confidence: 96%